Breast and cervical cancer patients' experience in Addis Ababa city, Ethiopia: a follow-up study protocol. Issue 4 (9th April 2019) - Gebremariam, Alem; Addissie, Adamu; Worku, Alemayehu; Hirpa, Selamawit; Assefa, Mathewos; Pace, Lydia E; Kantelhardt, Eva Johanna; Jemal, Ahmedin
Abstract : Introduction: Cancer is an emerging public health problem in Ethiopia, with breast and cervical cancers accounting for over half of all newly diagnosed cancers in women. The majority of women with breast and cervical cancer are diagnosed at late stage of the disease and most patients do not receive care consistent with global standards. However, little is known about the health-seeking behaviours, barriers to early detection and treatment, patient-reported outcomes, financial burden and survival of women with breast and cervical cancer in the country. Therefore, this study aims to document the experience of women with breast and cervical cancer from recognition of symptoms to diagnosis, treatment and survivorship/mortality in Addis Ababa city, Ethiopia. Methods and analysis: A prospective follow-up study using mixed methods (both quantitative and qualitative) will be employed. All women newly diagnosed with breast and cervical cancer from 1 January, 2017 to 30 June 2018 in Addis Ababa will be included in the study. Interviewer-administered questionnaires will be used to collect information about medical consultations after recognition of symptoms, health-seeking behaviours, treatment received, barriers to early detection and treatment, and survivorship care. In-depth interview will be conducted on purposefully selected women with breast and cervical cancer. The primary outcomes of the study are time intervals (patient and diagnostic waiting times), stage at diagnosis and survival. Multivariable analysis will be employed to determine the contributions of independent variables on the outcomes of interest. HRs with 95% CIs will be calculated for time-to-event outcomes. Qualitative data will be analysed using thematic analysis. Ethics and dissemination: This protocol is ethically approved by Institutional Review Board of Addis Ababa University. Verbal informed consent will be obtained from study participants. Results will be disseminated in international peer-reviewed journals and presented in relevant conferences.